"I Love This Story!" Examining Parent-Child Interactions during Storybook Reading. Issue 3 (3rd April 2021) - Patel, Shaneha; Segal, Aviva; Martin-Chang, Sandra
ABSTRACT: The home environment is an important contributor to children's literacy experiences. One activity that is frequently investigated is parent-child storybook reading. The present study examined book-reading interactions between 60 parent-child dyads. The sessions were recorded and parent-child behaviors were coded for types of talk (immediate, non-immediate, illustration production) and engagement. Research Findings : Results of hierarchical multiple regressions demonstrated that parents' non-immediate talk and engagement accounted for unique variance in children's non-immediate talk and engagement, above and beyond children's own behaviors. Parallel regressions demonstrated that children's non-immediate talk and engagement also accounted for unique variance in parents' non-immediate talk and engagement, above and beyond parents' own behaviors. Practice or Policy : These findings demonstrate that parents and children take on reciprocal roles during storybook reading. Implications for parents' practices are discussed.